PELAYAN PUBLIK DI KANTOR KELURAHAN INDUSTRI TENAYAN KECAMATAN TENAYAN RAYA KOTA PEKANBARU TAHUN 2018 - Rudi Hartono; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Public services at the village office are the spearhead in providing services to the community. To achieve quality service, reliable human resources are needed. Absence of employees and lengthy administrative arrangements indicate the need to improve the quality of Human Resources as the main actors in providing services. Lack of employee discipline because they are rarely present in the office is also an obstacle that will become an obstacle in providing a quality service. This research approach used is a qualitative approach, this type of research is descriptive. The research location is in Pekanbaru City, precisely in the Tenayan Industrial Village Office, Tenayan Raya District. And the technique of data collection is done by means of interviews and documentation. The results of this study are that the implementation of public services at the Tenayan Raya Industrial Village Office, Tenayan District, Pekanbaru City in 2018 still needs to be improved so that people who want to get services feel that what are the obstacles in administrative arrangements will no longer occur. Long-winded and likes to delay the completion of correspondence, the Lurah is rarely in place and discriminatory attitudes should not occur again so that people who want to get service feel that they are getting excellent and quality service at the Lurah Office for Industrial Village, Tenayan Raya District, Pekanbaru City. Keywords: Public Service, Tenayan Industrial Village Office